An acoustic investigation of primary and secondary lexical stress of Urdu - Qurrat Ul Ain; Mahmood, Muhammad Asim; Muslim Raza, Syed Muhammad; Zakir, Anam (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper investigated acoustic correlates of primary and secondary stress in Urdu language. Urdu is not a sufficiently researched language in the context of lexical stress. A few researches (Mehrotra, 1965; Hussain, 1997; Nair, 1999; Mumtaz, 2014, and Qurrat-Ul-Ain & Mahmood (2017) discussed stress in Urdu/Hindi language. Perhaps, Qurrat-Ul-Ain & Mahmood (2017) study is the first to phonetically document the presence of secondary stress in Urdu using the cue of duration. The present study focused on the four popular acoustic cues of lexical stress to see how Urdu lexical stress (primary as well as secondary) behaves against these cues. The stimuli of the study consist of six tri-syllabic words (embedded with low-back-long vowel /a:/ in all syllables) uttered by nine female Urdu speakers from Lahore. Four popular stress cues (duration, vowel quality, pitch, and intensity) have been analyzed to see their correlation with Urdu lexical stress. The analysis reveals three levels of lexical stress: primary, secondary, and unstressed. Vowel duration is the strongest cue to correlate with the levels of stress in Urdu while stressed segments prone to have higher values of intensity. Overall, a trend of lower F0 and higher formant values could be seen against stressed syllables. The study, however, needs to be expanded further by using words having other vowel sounds. Moreover, the phenomenon of word final lengthening can be taken into account in the potential researches.